Influence of the Amazon River runoff on the tropical atlantic - Masson, S; Delecluse, P (Physics and chemistry of the earth. Part B, Hydrology, oceans and atmosphere, 2001)
The Amazon river has the biggest flow in the world, 0.2 Sv (1 Sv = 106 m3/s), and is responsible for a large part of the low Sea Surface Salinity (SSS) in the west tropical Atlantic ocean. Very few Ocean General Circulation Model (OGCM) include runoff which brings a specific contribution to the Ocean physics. Comparison of simulations with constant or monthly runoffs shows that the spread of the Amazon fresh waters offshore of the north Brazilian coast is controlled by the ocean circulation and not by the Amazon flow. Therefore, in the model like in the observations, SSS minimum is observed in summer three months after the Amazon flood. In agreement with observations, a thick (more than 40 m) Barrier Layer (BL) is present every summer north of the Amazon mouth. Because of the strong and shallow salinity gradient associated with the Amazon freshwater, an important part of the solar radiation is trapped in the BL and creates an inversion of the vertical gradient of temperature. However with this forced model, BL does not seem to have a clear impact on SST and so on the air-sea interaction. Freshwater flux is also able to bend the sea surface. The geostrophic part of the North Brazilian Current (NBC) retroflection is then lightly weaker in presence of the Amazon runoff.